Greek mythology in Byzantine art - Weitzmann, Kurt, 1904-1993 (Princeton legacy library., 1984)
Kurt Weitzmann demonstrates that the postulated miniatures of the handbook that goes under the name of Apollodorus migrated into other texts, of which the commentary of Pseudo-Nonnus--attached to several homilies of Gregory of Nazianzus--and the Cynegetka of Pseudo-Oppian are the most important. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these.